Design Concept of Loyalty Program for E-Payment Method - Albert Miliano, Ignatius Steven, Zahid Abdurrahman Wirahaditenaya, Emil R. Kaburuan, Gunawan Wang, Sfenrianto (International Journal of Control and Automation, 2020)
Technology thrive in this modern age, leading to many changes in the way of how people go with their daily lives. Many people nowadays utilize technology to achieve their daily task, this technology helps them achieve it faster and more effortless. One of those activities are payment. There are a lot of financial technology companies in Indonesia, for example Go-Pay, OVO, DANA, etc. Each one of them trying to maintain their customer base staying loyal to them. One of the strategies was creating a loyalty program with a gamification concept and it has proven to be successful in maintaining their loyal customer. Although problem still exist where certain merchant only accepts certain e-Wallet and certain promotion only applied to certain e-Wallet. Author propose a super app design where it can be used to make a transaction in almost all merchant with only 1 barcode then the user can choose from which e-Wallet to use.